Flow features and truth scale based single-ended objective assessment of perceived quality of VoIP service - CHENG Wei-qing1; GONG Jian1; DING Wei1 (Tongxin xuebao)
A noninvasive,single-ended objective quality assessment method called "FSPAV",which only utilized IP flow features to predict the perceived quality of VoIP service （PQoS） was proposed. The cores of the method are three PQoS related metrics of flow features. It only needs to monitor IP packets containing voice data from the peer user received by a local end user to calculate metrics,with no need to synchronize clocks or parse application protocols. A measure of the individual truth grad is used to map the measurement values of three metrics on a call segment into a single speech qual-ity prediction. During the calculation,the goodness grad for each flow feature can also be derived. Talk experiments on the Internet by using VoIP software QQ and Skype was presented. The experimental results show that the objective as-sessments correlate well with subjective ones,which indicates that the method proposed here is effective.